The dominant strategies used within - Mazibuko, Beauty (My University, 2011)
Competitive strategy remains crucial for businesses, as it determines success in the market. However, exactly what strategy to employ in a company within a specific industry is a difficult task for practitioners. In the 1980’s, Porter (1985) described three “generic” strategies that would allow a company to be more competitive relative to others in the same industry. Although Porter’s (1985) strategy types have become the foundation for much of the business policy research in the past twenty years, theorists and researchers alike continue to debate over the appropriateness of these strategies in the current competitive environment bombarded with technology. This research seeks to identify dominant competitive strategies in the South African (SA) clothing retail industry and further validate the usage of Porters “generic” strategies. The study expands to understand whether different size companies use similar strategies or not. A structured questionnaire was sent out to clothing retail companies of sample size of 145 participants for them to identify the most appropriate competitive method on their business. The results from the common factor analysis indicated that three major strategies used in the industry namely, lean competitor, mix markets and core competencies. Further, it was identified that some strategies are associated with the size of the company while others are not
MBA - WBS
Keywords: Retail industries; Strategic planning